Fleet tactics and naval operations - Hughes, Wayne P., 1930-; Girrier, Robert, 1961- (U.S. Naval Institute blue & gold professional library., 2018)
"This book covers battle tactics at sea from the age of fighting sail to the present, with emphasis on trends (factors that have changed throughout history), constants (things that have not changed), and variables (things pertinent to each individual battle). The third edition highlights advances in unmanned vehicles, artificial intelligence, cyber warfare in peace and war, and other effects of information warfare and how they are changing the ways that battles at sea will be fought and won. It also describes the interaction between naval operations, wartime campaigns, and coalition tactics and their effects on war at sea and points out the growing interaction between land and sea in littoral combat."--Provided by publisher.